The Nature of the Word in Philosophical Prose of Russian Classics - Eremejev, Alexander Emmanuilovich; Akelkina, Elena Alekseevna; Kopteva, Eleonora Ivanovna; Kosyakov, Gennadiy Viktorovich (Journal of History Culture and Art Research, 2020)
The study discusses and systematizes various features and methods of word generalization in the fictional philosophical prose of Russian writers. The research methodology for the phenomenon of philosophical prose in Russian literature was developed throughout several decades, including the scholarship of Omsk scientists. The identity of the philosophical word is an acute problem, which is generally due to the actively continuing development of philosophical prose in contemporary literature. The study of philosophical prose is based on all the key methods of literary text analysis developed in Russian literary studies: holistic analysis, comparative historical method, genetic analysis, mythopoetic analysis, etc. At the same time, the analysis of philosophical prose needs to meet the case of logical and figurative principle correlation within the artistic thinking of the author. The genre and style analyses are necessary for understanding the synthesis of artistic traditions in philosophical prose. The analysis of rhetorical techniques in conjunction with the analysis of metaphors, allegories, and symbols contributes to the understanding of the specifics of generalization in philosophical prose. Understanding the genesis and evolution of philosophical prose allows the authors to trace how the concept of life-building, which is very characteristic of the national literary tradition, is transformed into an auto concept of philosophical prose of such authors as A. S. Pushkin, V. F. Odoyevsky, A. I. Herzen, F. M Dostoevsky, and others. The study demonstrates that philosophical prose responds to the most important spiritual, generally cultural phenomena; its literary tradition establishes human life experience as the object of its image. The subject of reflection simultaneously becomes an object. A reflecting consciousness is not only depicted but studied as well in this paper. This also applies to the forms of thinking, including those experiencing a spiritual crisis. Philosophical prose is often implemented in marginal literary genres and forms that are genetically related to the didactic allegorical tradition: anecdote, parable, diatribe, maxim, sermon, etc. The works of distinguished authors usually take the form of philosophical prose such as “Russian Nights” by V. F. Odoevsky, “My Past and Thoughts” by A. I. Herzen, “A Writer's Diary” by F. M. Dostoevsky. This paper demonstrates numerous approaches to the analysis of these literary works.